Information method of optimization parameters in the diagnosis of gas turbine engines - G. S. Zontov (Naučnyj Vestnik MGTU GA, 2016)
This article describes an algorithm parameter optimization method for the diagnosis of GTD in order to devide zones of efficiency. The autor focuses on the retional combination of methods of mathematical analysis and statistics and de-veloping an algorithm that allows to optimize the use of mathematical methods by longitudinal data collection and ma-chine learning.